Pemodelan Kesesuaian Habitat Mandar Gendang (Habroptila wallacii) di Pulau Halmahera, Indonesia - Aldiansyah, Septianto; Madani, Ilyas; Risna, Risna; Saputra, Randi Adrian (Jurnal Ilmu Kehutanan, 2025)
Drummer Rail (Habroptila wallacii) is a bird species of the Rallidae family with limited ecology and behavior information. The information on the distribution of H. wallacii in Halmahera Island is crucial as it is classified as a vulnerable species. Therefore, this research aims to predict the potential distribution of H. wallacii on Halmahera Island using the Maximum Entropy (MaxEnt) modeling method, which projects species distributions based on presence data and environmental variables. A total of 47 data points on H. wallacii encounters were obtained from open-access data sources and field observation. The variables used were land use land cover (LULC), normalized difference vegetation index (NDVI), elevation, slope, and proximity data (river). The results showed that 33.52% of the area was very suitable for H. wallacii habitat, 32.97% was suitable, and 33.50% was unsuitable. Approximately 29.39% of the suitable habitat was located in limited-production forest areas, while conservation areas covered only 5.19%. These results suggested the need to review spatial planning policies to increase protection of the natural habitat of the species. The results could serve as considerations and recommendations for the Ministry of Environment and Forestry regarding the future management of forest areas for these species.